The Identification of Phytohormone Receptor Homologs in Early Diverging Fungi Suggests a Role for Plant Sensing in Land Colonization by Fungi - Hérivaux, Anaïs (mBio, 2017)
Histidine kinases (HKs) are among the most prominent sensing proteins studied in the kingdom Fungi. Their distribution and biological functions in early diverging fungi (EDF), however, remain elusive. We have taken advantage of recent genomic resources to elucidate whether relationships between the occurrence of specific HKs in some EDF and their respective habitat/lifestyle could be established. This led to the unexpected discovery of fungal HKs that share a high degree of similarity with receptors for plant hormones (ethylene and cytokinin). Importantly, these phytohormone receptor homologs are found not only in EDF that behave as plant root symbionts or endophytes but also in EDF species that colonize decaying plant material. We hypothesize that these particular sensing proteins promoted the interaction of EDF with plants, leading to the conquest of land by these ancestral fungi.